P-167 Telehealth pilot: development and setting up of a telehealth service for palliative care patients. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Randall, Emma
Abstract : Weldmar Hospicecare has growing numbers of patients being referred to the service who want to be supported in their own homes for as long as possible. Weldmar are working in partnership with Macmillan who are providing funding for an 18 month secondment post to set up and lead a telehealth pilot. Therefore enhancing the service offered to Weldmar patients and giving clinicians another tool to support and monitor patients. Telehealth is already being used in the UK for patients with long term conditions such as COPD and heart failure but there are limited numbers of palliative care patients using a telehealth service. The pilot consists of a POD which has a protocol uploaded to it that has been written using recognised palliative care outcome measures; these are the Barthel Index and the IPOS scoring system. Patients log on daily completing the pre-set questions – this will monitor changes in symptoms and also level of need. The results are stored on the POD so clinicians visiting the home can access these, or have the option to access them remotely from their PC to review the data the patient has inputted. The PODs have the capability for video-conferencing and allow clinicians to use this to discuss with patients the data they have inputted and also carry out assessments of patients face to face via Skype. Patients have embraced the pilot and use of the POD. They report the POD is quick and easy to use, they like that clinicians can monitor them remotely. Clinicians are adapting to having another tool to use to support patients and having access to a wealth of data about patients. Also having the ability to monitor changes in symptoms without being reliant on patients relaying to them how they have been over a set period of time.